Network innovation through OpenFlow and SDN principles and design - Hu, Fei 1972- (CRC Press, 2014)
"Preface Software-defined network (SDN)/OpenFlow research and development have attracted the attention of many researchers and companies. The key idea of an SDN is to split the network forwarding function, performed by the data plane, from the network control function, performed by the control plane. This allows a simpler and more flexible network control and management, and also network virtualization. OpenFlow is the main SDN implementation. The network controller communicates with OpenFlow switches using the OpenFlow protocol through a secure channel. Using this connection, the controller is able to configure the forwarding tables of the switch. The figure (in the right) shows a simple OpenFlow architecture. OpenFlow-based SDN technologies enable us to address the highbandwidth, dynamic nature of computer networks; adapt the network functions to different business needs easily; and reduce network operations and management complexity significantly. Many large companies (such as Cisco, Microsoft, Google, etc.) have produced OpenFlow-supported products (such as switches). K16575_C000e.indd 11 11/12/2013 5:45:58 AM xi i Preface Channel Open flow Switch Controller OpenFlow Protocol Flow table Group table Flow table Flow table Needless to say, SDN/OpenFlow will become one of the most important trends for the future Internet and regional networks"--
Includes bibliographical references and index. - Print version record
Keywords: Software-defined networking (Computer network technology); OpenFlow (Computer network protocol); Réseaux SDN; OpenFlow (Protocole de réseaux d'ordinateurs); COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference